Heat-Induced Cytokinin Transportation and Degradation Are Associated with Reduced Panicle Cytokinin Expression and Fewer Spikelets per Panicle in Rice - Wu, Chao; Cui, Kehui; Wang, Wencheng; Li, Qian; Fahad, Shah; Hu, Qiuqian; Huang, Jianliang; Nie, Lixiao; Mohapatra, Pravat K.; Peng, Shaobing (Frontiers in Plant Science, 2017)
Cytokinins (CTKs) regulate panicle size and mediate heat tolerance in crops. To investigate the effect of high temperature on panicle CTK expression and the role of such expression in panicle differentiation in rice, four rice varieties (Nagina22, N22; Huanghuazhan, HHZ; Liangyoupeijiu, LYPJ; Shanyou63, SY63) were grown under normal conditions and subjected to three high temperature treatments and one control treatment in temperature-controlled greenhouses for 15 d during the early reproductive stage. The high temperature treatments significantly reduced panicle CTK abundance in heat-susceptible LYPJ, HHZ, and N22 varieties, which showed fewer spikelets per panicle in comparison with control plants. Exogenous 6-benzylaminopurine application mitigated the effect of heat injury on the number of spikelets per panicle. The high temperature treatments significantly decreased the xylem sap flow rate and CTK transportation rate, but enhanced cytokinin oxidase/dehydrogenase (CKX) activity in heat-susceptible varieties. In comparison with the heat-susceptible varieties, heat-tolerant variety SY63 showed less reduction in panicle CTK abundance, an enhanced xylem sap flow rate, an improved CTK transport rate, and stable CKX activity under the high temperature treatments. Enzymes involved in CTK synthesis (isopentenyltransferase, LONELY GUY, and cytochrome P450 monooxygenase) were inhibited by the high temperature treatments. Heat-induced changes in CTK transportation from root to shoot through xylem sap flow and panicle CTK degradation via CKX were closely associated with the effects of heat on panicle CTK abundance and panicle size. Heat-tolerant variety SY63 showed stable panicle size under the high temperature treatments because of enhanced transport of root-derived CTKs and stable panicle CKX activity. Our results provide insight into rice heat tolerance that will facilitate the development of rice varieties with tolerance to high temperature.